2014
DOI: 10.1111/bph.12863
|View full text |Cite
|
Sign up to set email alerts
|

1E7‐03, a low MW compound targeting host protein phosphatase‐1, inhibits HIV‐1 transcription

Abstract: BACKGROUND AND PURPOSEHIV-1 transcription is activated by the Tat protein which recruits the cyclin-dependent kinase CDK9/cyclin T1 to TAR RNA. Tat binds to protein phosphatase-1 (PP1) through the Q 35 VCF 38 sequence and translocates PP1 to the nucleus. PP1 dephosphorylates CDK9 and activates HIV-1 transcription. We have synthesized a low MW compound 1H4, that targets PP1 and prevents HIV-1 Tat interaction with PP1 and inhibits HIV-1 gene transcription. Here, we report our further work with the 1H4-derived co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 39 publications
1
75
1
Order By: Relevance
“…5D). Our recent study showed that mice injected with 25 mg/kg 1E7-03 accumulated 90 M plasma concentration of the compound up to 8 h (25). Thus, concentrations of 10 and 3 M, which effectively suppress replication of EBOV in vitro (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…5D). Our recent study showed that mice injected with 25 mg/kg 1E7-03 accumulated 90 M plasma concentration of the compound up to 8 h (25). Thus, concentrations of 10 and 3 M, which effectively suppress replication of EBOV in vitro (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…First, our recent study showed that PP1-targeted compound 1H4 did not prevent the interaction of PP1 with major regulatory subunits, such as NIPP1 or PNUTS (13). Second, we recently demonstrated that high doses of 1E7-03 administered to mice by injections do not result in a toxic effect (25). Third, a stable expression of PP1-sequestering cdNIPP1, although inhibitory for HIV-1, did not compromise cell growth (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently developed a library of PP1-targeting small molecules that were modeled to fit the RVxF-accommodating cavity of PP1 [69]. Our virtual screening of 300,000 compounds identified a tetrahydroquinoline derivative, 1E7-03 [70], that was devoid of toxicity, and displayed a half-life greater than 8 h when administered to mice. 1E7-03 bound to PP1 in vitro and prevented shuttling of PP1 into the nucleus [70].…”
Section: Inhibition Of Viral Transcription and Replicationmentioning
confidence: 99%
“…Our virtual screening of 300,000 compounds identified a tetrahydroquinoline derivative, 1E7-03 [70], that was devoid of toxicity, and displayed a half-life greater than 8 h when administered to mice. 1E7-03 bound to PP1 in vitro and prevented shuttling of PP1 into the nucleus [70]. 1E7-03 increased EBOV VP30 phosphorylation and effectively suppressed replication of EBOV particles in cultured cells [59].…”
Section: Inhibition Of Viral Transcription and Replicationmentioning
confidence: 99%